Little green [compact disc, unabridged] : an Easy Rawlins mystery - Mosley, Walter (Mosley, Walter. Easy Rawlins mystery., 2013)
Surviving a near-fatal car wreck and cruising the streets of the Sunset Strip during the late 1960s, Easy Rawlins investigates the disappearance of a young African-American, a case that is complicated by Rawlins's changing perspectives.